Process water geochemistry at the Kiirunavaara iron mine, northern Sweden - Westerstrand, Magnus (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2009)
Understanding process water characteristics and variations is important for ensuring the quality of mineral processing of iron ore. Large amounts of water are used, and the quality of the water can be crucial for processes such as flotation, agglomeration and balling. In this study, changes and variations in process water geochemistry at the Kiirunavaara iron mine have been studied in a time series from 1989 to 2008. Long-term trends at single sampling stations in the process chain as well as changes along the process chain have been studied by statistical methods. This study also quantifies the amounts of major elements such as Ca, Mg, Na, S and Cl carried by process water and by magnetite grain surfaces to the end product, iron ore pellets made from magnetite ore.Ca, S, Na and Cl are the major elements in the process water, accounting for over 80% of the dissolved concentration. Ca has the highest concentrations with an average of 183 mg/l and a maximum of 303 mg/l in the clarifying pond. Corresponding values for S are 162 and 292 mg/l for Cl 132 and 250 mg/l and for Na 88 and 172 mg/l. At all investigated sampling stations (ingoing water and water in the sorting plant, concentration plant, pelletizing plant and clarifying pond) dissolved elemental concentrations increase over the time period. This increase is mainly caused by the increase in production. It is probable that the high concentrations of Ca and S are results of sulfide oxidation and calcite buffering in the drainage area, while the main source of Na, Cl, K and Mg is fluid inclusions liberated during milling of the ore. A prediction of future concentrations of Ca in the process water shows that in future production planning, it will be important to calculate on the basis of higher concentrations in the process water in the whole process chain than are present today. In addition, the amount of colloids (0.22µm – 1kD) in the process water was examined by ultrafiltration. The amounts of various elements sorbed to the magnetite surfaces were estimated ...